Evaluation and management of cases of primary amenorrhoea with MRKH syndrome - Akhter, Nasreen; Begum, Badrunnesa (Bangladesh Medical Journal Khulna, 2013)
The Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome, the second most common cause of primary amenorrhoea usually remains undetected until puberty and is characterized by congenital aplasia or hypoplasia of the uterus and most of the vagina in women showing normal secondary sexual characteristics. MRKH syndrome may be isolated (type I) but is more frequently associated with renal, vertebral, and, to a lesser extent, auditory and cardiac defects (MRKH type II or MURCS association). Complete evaluation of MRKH patient includes genital, urinary tract, cardiac, spinal and auditory assessment which need multidisciplinary approach. This review is an attempt to discuss the subtypes, associated anomalies, diagnostic consideration and treatment recommendations of patients with MRKH syndrome and aimed to make the specialists of other discipline, general physicians and the gynaecologists well aware about the entity. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13626 Bang Med J (Khulna) 2012; 45 : 24-29